2006
DOI: 10.1007/s00122-006-0363-6
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of single-cross hybrid performance for grain yield and grain dry matter content in maize using AFLP markers associated with QTL

Abstract: Prediction methods to identify single-cross hybrids with superior yield performance have the potential to greatly improve the efficiency of commercial maize (Zea mays L.) hybrid breeding programs. Our objectives were to (1) identify marker loci associated with quantitative trait loci for hybrid performance or specific combining ability (SCA) in maize, (2) compare hybrid performance prediction by genotypic value estimates with that based on general combining ability (GCA) estimates, and (3) investigate a newly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
58
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 15 publications
7
58
0
Order By: Relevance
“…Therefore, the results of our quantitative genetic investigations show that in the absence of epistasis divergent heterotic groups lead to a predominance of s 2 GCA over s 2 SCA . These theoretical findings are in accordance with experimental data of genetically divergent heterotic groups in various crops such as maize (Schrag et al 2006), rye (Miedaner and Geiger 1996), and sunflower (Kaya 2005) and explain the high prediction accuracy of hybrid performance based on GCA effects. A* refer to the dominance and additive variance for the strategy of sampling the heterotic groups out of one synthetic established using both heterotic groups.…”
supporting
confidence: 87%
“…Therefore, the results of our quantitative genetic investigations show that in the absence of epistasis divergent heterotic groups lead to a predominance of s 2 GCA over s 2 SCA . These theoretical findings are in accordance with experimental data of genetically divergent heterotic groups in various crops such as maize (Schrag et al 2006), rye (Miedaner and Geiger 1996), and sunflower (Kaya 2005) and explain the high prediction accuracy of hybrid performance based on GCA effects. A* refer to the dominance and additive variance for the strategy of sampling the heterotic groups out of one synthetic established using both heterotic groups.…”
supporting
confidence: 87%
“…The most likely explanation for the high prediction accuracies generally observed is that both H 2 and the realized relationships among parental lines tend to be very high in commercial maize breeding programs. For example, our high estimates of H 2 were for both traits in close agreement to those of Schrag et al (2006) and Massman et al (2013), the latter of which analyzed data from a U.S. corn-belt breeding program. Massman et al (2013) also found similarly high pairwise realized relationships to those in our study (details not shown).…”
Section: Prediction Accuracy Of T2 T1 and T0 Hybridssupporting
confidence: 64%
“…This kind of simulation could reflect real situations of random unbalance obtained in field crosses. Nonetheless, some recent papers have proposed using more predictor parentals in the cross-validation process in order to increase the prediction efficiency (Vuylsteke et al, 2000;Schrag et al, 2006). Although this procedure increases the prediction efficiency, it does not resolve the breeder's need to predict non-evaluated crosses even when their genitors are not among the set of appraised hybrids.…”
Section: Discussionmentioning
confidence: 99%
“…In all these studies, a relatively good correlation between phenotypic means and predicted means was observed, demonstrating acceptable accuracy. The prediction accuracy is dependent on the heritability of traits in the tested hybrids, adequate estimates of variance components, accurate approximation of relationship coefficients by molecular markers (Balestre et al, 2009), and number of predictor parentals in the analysis (Vuylsteke et al, 2000;Schrag et al, 2006). Some authors suggest the use of molecular marker information associated with similarity-by-state coefficients for genotypic value prediction (Bauer et al, 2006;Balestre et al, 2008).…”
Section: Introductionmentioning
confidence: 99%